The Opioid Rotation Ratio of Hydrocodone to Strong Opioids in Cancer Patients. (23rd October 2014) - Reddy, Akhila; Yennurajalingam, Sriram; Desai, Hem; Reddy, Suresh; Cruz, Maxine; Wu, Jimin; Liu, Diane; Rodriguez, Eden Mae; Waletich, Jessica; Shin, Seong Hoon; Gayle, Vicki; Patel, Pritul; et al.
Abstract: Purpose: Cancer pain management guidelines recommend initial treatment with intermediate-strength analgesics such as hydrocodone and subsequent escalation to stronger opioids such as morphine. There are no published studies on the process of opioid rotation (OR) from hydrocodone to strong opioids in cancer patients. Our aim was to determine the opioid rotation ratio (ORR) of hydrocodone to morphine equivalent daily dose (MEDD) in cancer outpatients. Patients and Methods: We reviewed the records of consecutive patient visits at our supportive care center in 2011–2012 for OR from hydrocodone to stronger opioids. Data regarding demographics, Edmonton Symptom Assessment Scale (ESAS), and MEDD were collected from patients who returned for follow-up within 6 weeks. Linear regression analysis was used to estimate the ORR between hydrocodone and MEDD. Successful OR was defined as 2-point or 30% reduction in the pain score and continuation of the new opioid at follow-up. Results: Overall, 170 patients underwent OR from hydrocodone to stronger opioid. The median age was 59 years, and 81% had advanced cancer. The median time between OR and follow-up was 21 days. We found 53% had a successful OR with significant improvement in the ESAS pain and symptom distress scores. In 100 patients with complete OR and no worsening of pain at follow-up, the median ORR from hydrocodone to MEDD was 1.5 (quintiles 1–3: 0.9–2). The ORR was associated with hydrocodone dose ( r = −.52; p < .0001) and was lower in patients receiving ≥40 mg of hydrocodone per day ( p < .0001). The median ORR of hydrocodone to morphine was 1.5 ( n = 44) and hydrocodone to oxycodone was 0.9 ( n = 24). Conclusion: The median ORR from hydrocodone to MEDD was 1.5 and varied according to hydrocodone dose. Abstract : Cancer pain management guidelines recommend initial treatment with intermediate-strength analgesics such as hydrocodone and subsequent escalation to stronger opioids such as morphine. The aim of this study was to determine the opioid rotation ratio (ORR) of hydrocodone to morphine equivalent daily dose (MEDD) in cancer outpatients. An ORR of 1.5 is suggested to calculate the MEDD of hydrocodone for doses <40 mg/day, and an ORR of 1 is suggested for doses ≥40 mg/day.